2017
DOI: 10.1016/j.jocrd.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The link between ADHD-like inattention and obsessions and compulsions during treatment of youth with OCD

Abstract: Attention-deficit/hyperactivity disorder (ADHD) has been found to be highly comorbid in children and adolescents with obsessive-compulsive disorder (OCD). Some have proposed, however, that obsessive anxiety may cause inattention and executive dysfunction, leading to inappropriate ADHD diagnoses in those with OCD. If this were the case, these symptoms would be expected to decrease following successful OCD treatment. The present study tested this hypothesis and evaluated whether ADHD symptoms at baseline predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Indeed, Abramovitch, Dar, Hermesh, and Schweiger () have suggested an ‘executive overload’ model for OCD, according to which obsessions represent attempts to control automatic processes, consequently consuming valuable cognitive resources and resulting in neuropsychological impairments. This model, suggesting that ADHD‐like symptoms are actually an epiphenomenon of OCD symptoms, is supported by the finding that treatment for OCD is related to a reduction in inattention symptoms (Guzick et al ., ). The executive overload model represents one possible explanation for the findings of the current study: Specifically, individuals characterized by OC symptoms probably score highly on absorption because they tend to immerse in obsessions or engage their full attention in compulsive mental rituals.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Indeed, Abramovitch, Dar, Hermesh, and Schweiger () have suggested an ‘executive overload’ model for OCD, according to which obsessions represent attempts to control automatic processes, consequently consuming valuable cognitive resources and resulting in neuropsychological impairments. This model, suggesting that ADHD‐like symptoms are actually an epiphenomenon of OCD symptoms, is supported by the finding that treatment for OCD is related to a reduction in inattention symptoms (Guzick et al ., ). The executive overload model represents one possible explanation for the findings of the current study: Specifically, individuals characterized by OC symptoms probably score highly on absorption because they tend to immerse in obsessions or engage their full attention in compulsive mental rituals.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, one study on a treatment‐seeking sample of patients with OCD demonstrated that dissociative absorption at the beginning of treatment was predictive of treatment non‐response (Rufer et al ., ). Interestingly, in a different study, baseline inattention symptoms were unsuccessful in predicting treatment response for youth with OCD (Guzick et al ., ). Thus, therapeutic implications should be considered.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous research has also found that comorbid ADHD may interfere with success in OCD treatment, with poorer treatment outcomes in cognitive behavioral therapy (CBT) [33]. However, a recent study [34] has found that when treating a child or adolescent with co-occurring OCD and clinically significant attention problems when OCD-onset clearly precedes ADHD-like inattention, clinicians may wish to target obsessive-compulsive symptoms first to have also inattention improved.…”
Section: Eo: a Neurodevelopmental Disorder Dimensions And Trajectoriesmentioning
confidence: 99%
“…In terms of co-morbid OCD–ADHD, there is evidence to support that treating OCD with SSRIs and cognitive behaviour therapy with exposure response prevention (CBT+ERP) improves attentional symptoms (38). This may be mediated through SSRI activation of BDNF and other neurotrophic factors that lead to neuronal growth in networks responsible for working memory and processing speed (3941).…”
Section: Treatment Implications For Co-morbid Ocd–adhdmentioning
confidence: 99%